Sculpted Bedrock Forms along the Niagara Escarpment, Niagara Peninsula, Ontario - Tinkler, Keith; Stenson, Ronald (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1992)
ABSTRACTAssemblages of subglacial sculpted bedrock forms (p-forms; Dahl, 1965) are identified on resistant units of the Niagara Escarpment in the Niagara Peninsula, and on the Onondaga Escarpment. The scale of the features is much larger than previously recorded for bedrock glacial features in the Peninsula (Feenstra, 1981) and we suggest that there is a continuous spectrum of forms from small obstacle marks with dimensions of a few centimetres, through ridges and furrows measured in tens of metres, to promontories on the order of kilometres. Such assemblages comprise fluted surfaces with a consistent orientation between N40E and N45E, and which show very little variation within a site. Mapping the features has increased our awareness of their extent, and of the problems they pose for mechanisms proposed to explain them. The morphometry of the forms is similar to that described elsewhere, and the irregular edge of the Niagara Escarpment to oncoming flows is thought to be responsible for the prominent features described. The apparent removal of substantial bedrock blocks implies flow velocity well in excess of 3 m/s. Therefore the sculpting of the forms is attributed to fast flowing subglacial meltwater which may have had a discharge of the magnitude of 2.1 x 106 cumecs.